1990
DOI: 10.1002/(sici)1097-4571(199009)41:6<408::aid-asi2>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Automatic syntactic analysis of free text

Abstract: Problems encountered under the syntactic analysis of free text documents are discussed. As these problems are of general interest in nonautomatic or automatic syntactic indexing or search systems, these problems are presented in detail. The system called COPSY (context operator syntax), which uses natural language processing techniques during fully automatic syntactic analysis (indexing and search) of free text documents is described. Applications under real world conditions are mentioned as well as evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…), Cass2: 1300-2300 w/s, Copsy: 2700? w/s [11]). Cass2 is as fast as any parser in this class, with the possible exception of Copsy, for which the hardware adjustment is highly uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…), Cass2: 1300-2300 w/s, Copsy: 2700? w/s [11]). Cass2 is as fast as any parser in this class, with the possible exception of Copsy, for which the hardware adjustment is highly uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the surface analysis and the analysis of fragments from the corpus, many systems effectuate a POS category disambiguation process (Kupiec, 1992). The syntactic variants identified through these methods can be grouped, finally, in canonical syntactic structures (Schwarz, 1990;Sheridan & Smeaton, 1992;Smadja, 1993;Strzalkowski, 1996).…”
Section: An Approach To Standardization Methods Of Termsmentioning
confidence: 99%
“…The retrieval results from syntactic relation matching appears to be no better than the results obtainable using index phrases generated using statistical methods, such as those described by Fagan (1989). Metzler & Haas (1989), Metzler, Haas, Cosic & Weise (1990), Schwarz (1990), and Ruge, Schwarz, & Warner (1991) performed syntactic processing to produce dependency trees that indicate which terms modify which other terms. Smeaton & van Rijsbergen (1988) found that the premodifier-headnoun relation (e.g., adjective-noun) has a bigger impact on retrieval than other relations.…”
Section: Relation Matching For Precision Enhancementmentioning
confidence: 99%